Costs associated with functional gastrointestinal disorders and related signs and symptoms in infants: a systematic review protocol. Issue 8 (24th August 2016) - Glanville, Julie; Ludwig, Thomas; Lifschitz, Carlos; Mahon, James; Miqdady, Mohamad; Saps, Miguel; Hock Quak, Seng; Lenoir-Wijnkoop, Irene; Edwards, Mary; Wood, Hannah; Szajewska, Hania
Abstract : Introduction: Functional gastrointestinal disorders (FGIDs) and FGID-related signs and symptoms have a fundamental impact on the psychosocial, physical and mental well-being of infants and their parents alike. Recent reviews and studies have indicated that FGIDs and related signs and symptoms may also have a substantial impact on the budgets of third-party payers and/or parents. The objective of this systematic review is to investigate these costs. Methods and analysis: The population of interest is healthy term infants (under 12 months of age) with colic, regurgitation and/or functional constipation. Outcomes of interest will include the frequency and volume of reported treatments, the cost to third-party payers and/or parents for prescribed or over the counter treatments, visits to health professionals and changes in infant formula purchases, and the loss of income through time taken off work and out of pocket costs. Relevant studies will be identified by searching databases from 2005 onwards (including MEDLINE, EMBASE, PsycINFO, NEXIS, DARE, Health Technology Assessment database, National Health Service Economic Evaluation Database and others), conferences from the previous 3 years and scanning reference lists of eligible studies. Study selection, data extraction and quality assessment will be conducted by two independent reviewers and disagreements resolved in discussion with a third reviewer. Quality assessment will involve study design-specific checklists. Relevant studies will be summarised narratively and presented in tables. An overview of treatments and costs will be provided, with any geographical or other differences highlighted. An assessment of how the totals for cost differ across countries and elements that contribute to the differences will be generated. Ethics and dissemination: This is a systematic review of published studies that will be submitted for publication to a peer-reviewed journal. Ethical committee approval is not required. Trial registration number: CRD42016033119.